Design of Active Front Steering (AFS) system with QFT control. (27th September 2011) - Zhang, Jingyi; Kim, Jinwan; Xuan, Dongji; Kim, Youngbae
This paper investigates a control strategy of active front wheel steering based on quantitative feedback theory (QFT). By incorporating feedback from yaw rate sensor into active steering system, the control system improves the dynamic responses of the vehicle. A multi degree-of-freedom nonlinear vehicle model is co-simulated with MATLAB Simulink and ADAMS/CAR. The performance of the control system is evaluated under various emergency manoeuvres and road conditions. The results show that the designed robust control algorithm has good control performance and can efficiently improve the handing qualities and stability characteristics.